"Yvonne Rorke, Patricia Rorke, Ernest Forward, Jim Rorke and Ralph Pike" - Rorke Family (1935)
Ernest Forward, in his garden at Harbour Rock Hill, Carbonear, with his grandchildren Yvonne (Rorke) Pratt, Patricia (Rorke) Yorke, and James Ernest Rorke, and Ralph Pike. Ernest Edward Forward (1859-1944), son of Capt. Mark William Forward and Mary (Bemister) Forward, was born at Carbonear on 29 May 1859. He married Tryphena Butt on 24 June 1885, and had three daughters: Ernestine, Hilda and Kathleen. Ernest Forward died on 14 April 1944. His daughter Kathleen married James Rorke on 23 May 1917 and had three children: Patricia (1918- ), James Ernest (1919-2005) and Yvonne Rorke (1922-1998). Ernest's other daughter Ernestine married Arthur S. Pike at Carbonear on 25 September 1913 and had 3 sons: Ernest (1914-1985), Arthur Jr. (1916-1985) and Ralph (1924-1985). The Rorke Family Photograph Collection contains 301 black and white and 28 colour photographs of the Rorke Family of Carbonear, Newfoundland, as well as the Forward and Bemister families from that area who are linked to it by marriage. Although spanning from the 1840s-1970s, most photos are from 1900-45, showing family events, homes and Newfoundland and Labrador locations. There is also an album of photos taken while James Rorke attended the Leys School in Cambridge, England.